Development and in-depth experimental characterization of novel TiZrNbHfTaOx reinforced 316L stainless steel for advanced nuclear applications - Guler, Omer; Albayrak, M. Gokhan; Basgoz, Oykum; Kavaz, E.; Alkarrani, Hessa; ALMisned, Ghada; Tekin, H. O. (Elsevier Science Sa, 2024)
Oxide Dispersion Strengthened (ODS) materials are known for their exceptional performance in hightemperature and radiation environments. This study explores the radiation shielding properties of 316L Stainless Steel reinforced with TiZrNbHfTaOx High-Entropy Oxide (HEO). By integrating HEOs into the 316L stainless steel matrix, we aim to enhance its structural and radiation shielding properties. The HEO was synthesized using high-energy ball milling and oxidation processes, followed by thorough characterization using X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy-dispersive spectroscopy (EDS). Our results indicate significant improvements in both gamma-ray and neutron shielding properties. The 316L SS samples reinforced with 20 % HEO exhibited the highest mass attenuation coefficients (MAC), lowest half-value layers (HVL), and highest effective atomic numbers (Zeff) across all tested photon energies. These enhancements are attributed to the high atomic number elements and unique synergistic effects of HEOs. Neutron shielding was evaluated through equivalent dose rate measurements, with the 20 % HEO sample demonstrating the highest absorbed dose rate percentage and superior neutron interaction cross-sections. Benchmarking against standard materials confirmed the superior performance of HEO-reinforced 316L SS, making it a promising candidate for advanced radiation shielding in nuclear reactors and other high-radiation environments. Our findings suggest that HEO reinforcement not only improves mechanical properties but also significantly enhances the radiation protection capabilities of 316L stainless steel.
Keywords: High-entropy oxide; Radiation; 316L stainless steel; Nuclear applications